Penguatan Kemampuan Literasi Digital dalam Pembelajaran Abad 21 di Sekolah Menengah Atas Labschool Palu - Charles Kapile; Nuraedah Nuraedah; Minarni Nongtji; Mutawakkil Mutawakkil; Fajar Nugroho (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to strengthen students’ digital literacy skills in addressing the challenges of 21st-century learning at SMA Labschool Palu. The program was implemented using a participatory and collaborative approach through socialization, training, and interactive mentoring activities that directly engaged students in the practical use of digital media for learning, particularly in history education. The program involved 35 students and was conducted over a four-day period. Evaluation instruments included documentation, interviews, observations, and pre-test and post-test assessments. Data were analyzed using descriptive quantitative and qualitative techniques. The results indicate that the program was implemented effectively and had a positive impact on improving students’ digital literacy skills. This improvement is reflected in an increase in the average pre-test score from approximately 76.4 (moderate category) to approximately 85.2 (high category). In addition, students were able to produce high-quality digital history posters, demonstrating a deep understanding of the learning materials and effective application of digital literacy in history learning.